Influence of organizational culture, work discipline and work motivation on the performance of East Nusa Tenggara province youth and sports officer employees - Neny Lorinda Kome; Cosmas Fernandez; Simon Sia Niha; M. E. Perseveranda; Yolinda Yanti Sonbay (Institute of Computer Science (IOCS), 2024)
This study is based on the indications of employees' low performance at the Office of Youth and Sports, East Nusa Tenggara Province and aims to know the significant effect of Organizational Culture, Work Discipline and Motivation on the Employees' Performance, both and partially, on the employees' performance. The data that were taken among 56 employees as respondents by distributing a questionnaire, were then analyzed using descriptive and inferential statistics – multiple linear regression, applying SPSS version 27. The results of descriptive statistics analysis indicated that organizational culture (90.44 %), work discipline (89.80 %), motivation (90.83 %) and employees' performance (91.47 %) are categorized as very good. The results of inferential statistics (t-test) show that organizational culture (0.001 < 0.05), work discipline (0.002 < 0.05) and motivation (0.002 < 0.05) partially have a positive and significant effect on the employees' performance. The results of F-test show that the three independent variables (105.365, sig. 0.000 < 0.05) simultaneously have a positive and significant effect on the employees' performance. The results of determination coefficient (R2) indicate that the three independent variables contribute 85.9 % on the employees' performance, while the rest of 14.10% are distributed by other variables excluded in this research.